INTERNALISASI NILAI-NILAI KARAKTER MELALUI KEGIATAN EKSTRAKURIKULER PRAMUKA (Studi Kasus di SDK Wae Kajong) - Vitalis Tarsan; Maria Imel Dafrosi; Remigius Baci (JIPD (Jurnal Inovasi Pendidikan Dasar), 2021)
Internalization of Character Values through Scout Extracurricular Activities (Case Study at SDK Wae Kajong). Humans with good character are the product of an educational process. Both formal and non-formal education. One of the formal education institutions that tries to produce with good character is basic education. One of the activities in basic education institutions, especially in elementary schools, which is full of internalization of good character values, is scouting extra-curricular activities. The purpose of this study was to describe the character values ​​that were developed and internalized through scout extracurricular activities at SDK Wae Kajong. This research is a qualitative research, case study design. The data sources of this research were human and non-human data sources. The collection techniques used were: (1) in-depth interviews, (2) observation, and (3) documentation study. The key instrument in this study is the researcher himself. Data were analyzed in three sub-processes, namely: data reduction, data presentation, and conclusion drawing. To ensure the validity and credibility of the data, the researchers examined the data by using triangulation of techniques and sources. The results showed that the values are fostered and lived through the scouts, in SDK Wae Kajong is confident, creative, conscientious, cooperative, communicative, dialogue, solution thinking, caring for nature, respect for others, self-contained, low liver, tolerant, strong, simple, solider, disciplined, neat, polite, agile, responsibility, leadership, self-control, to hear right of others, concentration, obey the rules, and curious .